Resolvemos problemas de adición de fracciones - Valverde Gamboa, Nancy (2019)
This sufficiency work has been prepared for boys and girls of the fourth grade of primary education, of the city of Trujillo in the year 2019, with the theme entitled We solve problems of addition of fractions, in which it has been taken into account that students will be able to understand the notion of fraction as part of a whole, they will also learn through a graphical representation what the concept of fraction of a number means and know how to calculate it, which will allow to successfully face the study of the addition of fractions ._x000D_ In the elaboration of the session we have worked with the pedagogical and didactic processes of the area of mathematics to promote significant learning._x000D_ The strategies used were designed to promote meaningful learning in their daily lives._x000D_ It is intended at all times to awaken the interest and motivation of the student in mathematics, as well as generate new knowledge through cognitive conflict so that children reach the expected level of achievement.